The Degree of Transformational Leadership Practice among Public and Private Secondary School Principals in the Capital Municipality of Sana’a - Al-Amrani, Abdulghani M. (University of Science and Technology Journal for Management and Human Sciences, 2024)
This study aimed to determine the degree to which transformational leadership dimensions are practiced by public and private secondary school principals in the Capital Municipality of Sana’a, from the perspective of teachers. A descriptive-analytical approach was employed to achieve the study’s objectives. The study sample consisted of (899) male and female teachers. Data was collected using a questionnaire, and a number of inferential statistical methods were used for analysis. The study found that the degree of transformational leadership practice among public and private school principals in the Capital Municipality of Sana’a, as perceived by teachers, was high, with a mean of (4.02). The dimensions were ranked in descending order as follows: (idealized influence, inspirational motivation, intellectual stimulation, individual consideration, and empowering teachers). The study also found statistically significant differences in the responses of the sample members regarding the degree of transformational leadership practice among public and private secondary school principals which could be attributed to the variable of teacher qualification and school type; the differences were in favor of the non-educational university qualification category and in favor of the private schools’ category. The results also showed that there were no statistically significant differences attributed to the variables of (school principal gender, teacher gender, and years of teaching experience). The study provided several recommendations in light of its findings, the most important of which is to hold training courses and professional development programs for principals to raise the level of their practice of transformational leadership behaviors.